2002
DOI: 10.1051/fruits:2002007
|View full text |Cite
|
Sign up to set email alerts
|

Déterminants de la production de plantain dans le sud-ouest du Cameroun : intérêt d'un observatoire

Abstract: -Introduction. Plantain is an important crop for food safety in sub-Saharan Africa. In order to treat the research priorities better on a hierarchical basis according to the producer constraints, a permanent observation unit was placed within the framework of an interdisciplinary approach. Materials and methods. A sampling in banana plantations was carried out in the zones of distinct agroecologic contexts which supply Douala (Cameroon). The data were obtained by a follow-up of parcels and holdings. On the par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 4 publications
1
4
1
1
Order By: Relevance
“…The lower overall fruit yield of the local plantains could also be due to higher susceptibility to pests and diseases compared with hybrid plantains. The average bunch weight of each improved genotype reported in this study is higher than that reported from farmers' fields in Cameroon (Banful et al, 2008;Dépigny et al, 2019;Pierrot et al, 2002). It is however below the average yield of 24.7 kg recorded in the plantain Optim trial done by CARBAP (S. .…”
Section: Discussioncontrasting
confidence: 72%
“…The lower overall fruit yield of the local plantains could also be due to higher susceptibility to pests and diseases compared with hybrid plantains. The average bunch weight of each improved genotype reported in this study is higher than that reported from farmers' fields in Cameroon (Banful et al, 2008;Dépigny et al, 2019;Pierrot et al, 2002). It is however below the average yield of 24.7 kg recorded in the plantain Optim trial done by CARBAP (S. .…”
Section: Discussioncontrasting
confidence: 72%
“…In light of the lack of a sufficient quantity of quality plantain material (suckers), farmers collect suckers from old plots that are lying fallow (80% of suckers), thereby transferring significant quantities of contaminated planting material to healthy plots. Production cycles last only 4 years and produce low yields, with losses amounting to more than 50% of production after the third cycle, resulting in a shift in the production area (Pierrot et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Former results [3] showed that, under smallholder conditions, losses of banana plants before harvest often surpass 30% of total banana plants initially planted. To get correct figures concerning yields, a sufficient number of bunches must be observed (20 to 30) and, consequently, other banana plants of the same variety, cycle and development stages must replace the ones lost.…”
Section: Resultsmentioning
confidence: 99%